Radical distrust: Are economic policy attitudes tempered by social trust? - Hans Pitlik; Martin Rode (Austrian Institute of Economic Research (WIFO), 2019)
Debates about the appropriate role of markets and governments are often shaped by sharply contrasting opinions. Based on individual data from the World Values Survey and the European Values Study for up to 190,000 respondents in a sample of 68 democratic countries, we find that social trust is associated with tempered attitudes regarding government intervention and redistribution. Results corroborate ideas from socio-psychological research that trusting people have personality attributes which work towards a moderation on politically divisive topics. Complementary to the existing literature on political polarisation, this opens the possibility that trusting societies may be superior at implementing controversial policy reforms because social trust reduces the probability of extreme attitude formation.
Keywords: D70; D78; Z13; 330; social trust; polarization; policy attitudes; preference formation